SCAPE: identification and selection of large‐scale migration tools and services - Castro, Rui (2011)
A preservation action is a concrete action, usually implemented by a software tool, that is performed on digital content in order to achieve some preservation goal. The execution of a preservation action has the purpose of supporting the continuous access to content or to make sure that digital preservation is being carried out effectively (Ferreira, Baptista, & Ramalho, 2006). For example, a migration of content from an obsolete format to a more up‐to‐date one, the replacement of a viewer application in some rendering environment, the execution of legacy software in an emulation environment, etc. Preservation actions have been extensively analysed and employed in experimental digital preservation systems (Eld Zierau & Caroline van Wijk, 2008; Ferreira, Baptista, & Ramalho, 2007). However, current approaches are not capable of coping with real‐size collections of today’s preservation environments, e.g. an e‐journal library may contain several thousands of documents adding up to several terabytes of information. A national‐wide Web archiving service will contain a myriad of unrelated formats and can easily host Petabytes of data. The Work package WP10 of SCAPE project (i.e. Action Services Components) is focused on the applicability of action tools and services to large collections of complex digital objects by analysing and improving interfaces and internal functionality of existing software tools, extending them and creating new functionality to cope with large‐scale digital preservation scenarios. Within this work package, tools will be enhanced to deal with, not only single file formats, but also compound objects, large‐sized objects and large collections of digital objects.